Sociotechnical imaginaries and digital orientalism in social media discourses about Asian “tech nations”: A critical exploration using computational methods - Nguyen, Dennis (Journal of digital social research, 2025)
Sociotechnical imaginaries and national imaginaries are intrinsically linked, as visions for the role of technology often go hand in hand with aspirations for economic growth and political power within specific countries. Discourses around Asian “tech nations” such as China and South Korea exemplify this dynamic, as they are frequently portrayed as technology leaders. Arguably, digital technologies have become prominent features in the portrayal and perception of nation states, while, simultaneously, expectations surrounding these technologies shape the sociotechnical imaginaries that emerge around them. A critical analysis of this relationship—and how it becomes manifest through framing practices in global media discourses—can reveal the extent to which oversimplified (mis)representations amount to forms of digital orientalism, particularly among foreign commentators. These include the selective emphasis on either predominantly negative or positive portrayals of Asian countries and their relationships with emerging technologies. Digital orientalist sentiments conflate sociotechnical and national imaginaries to promote highly selective representations of a given “Eastern” culture and its role in technological development. Social media platforms such as Twitter (now X) are important sites for such tech-nation discourses, featuring media commentators, politicians, entrepreneurs, and tech professionals. This article offers a critical analysis of discussions on Twitter about China, India, Japan, and South Korea in the context of digital technology. Using computational text analysis on a large sample of tweets from 2010 to 2021 (N = 2,077,232), the study explores how Asian countries are portrayed within the global Anglophone tech discourse and the extent to which they are subject to forms of digital orientalism. The findings highlight how online discourses, sociotechnical imaginaries, and national imaginaries intersect, with an emphasis on both commonalities and differences in the framing of Asian countries based on cultural, political, and economic factors.